Techno-economic analysis and eco-efficiency indicators of a biomass-solar hybrid renewable energy system for João Pinheiro City - Camila Fonseca Chaves Campos; Vanessa Aparecida de Sá Machado; Laene Oliveira Soares; Ronney Arismel Mancebo Boloy (Discover Sustainability, 2024)
Abstract The study aims to rapidly scale up Hybrid Renewable Energy System (HRES) specifically emphasizing bioenergy generation for isolated rural communities. It aims to identify the most profitable and efficient configuration for HRES biomass-solar in João Pinheiro, taking advantage of local eucalyptus production to reduce costs associated with the transport of biomass waste, considering energy, economic and ecological indicators. Eucalyptus waste was chosen as the source of biomass as fuel, the Downdraft gasifier with air as the gasification agent, and monocrystalline silicon technology was selected for photovoltaic modules. Two case study scenarios were proposed based on global efficiency calculations. The techno-economic analysis was applied based on the First Law of Thermodynamics and the Levelized Cost of Electricity (LCOE) method. Case 2 showed the overall energy efficiency of 17.43% and LCOE 0.034 US$/kWh more suitable for HRES solar-biomass technology. Additionally, the eco-efficiency indicator indicator based on the calculated Net Present Value and ecological efficiency indicator, allowed evaluation of the relationship between added value and the environmental impacts associated with the studied configurations, with case 2 presenting 9.28e−05 kgCO2/US$ as best result. The conclusions show that the techno-economic analysis applied to the HRES syngas-solar, along with the eco-efficiency indicator, presents the viability of decentralized bioenergy supply, particularly in isolated rural communities. This innovative approach encourages sustainable measures to meet energy needs in isolated regions with climatic, environmental and biomass supply conditions like those of João Pinheiro.